PRESERVATION OF THE GENE POOL OF PLANTS UNDER IN PERMAFROST CONDITIONS: STATE, ADVANTAGES, AND PROSPECTS - B. M. Kershengolts; I. F. Zhimulev; N. P. Goncharov; R. V. Chzhan; G. V. Filippova; A. A. Shein; I. A. Prokopiev (Вавиловский журнал генетики и селекции)
The effect of long-term storage of seeds of three leguminous species (Pisum sativum, Lens culinaris, and Cicer arietinum) on physiological (germination) and cytological (mitotic index) parameters of seeds and seedlings derived from them was studied. It was found that after nearly 35 years of storage in permafrost (temperature from –5,5 to –6,0 °C), without seeding, the germination of seeds of varieties of the species studied maintained at the same or slightly lower level than in reference samples (seeds of the same cultivars harvested in 2007–2009), and no significant difference in the growth rate of roots was recorded. The observed number of chromosomal aberrations in root meristem cells did not increase, except P. sativum cv. Latores and L. Culinaris cv. k-2330, and in these cases neither the laboratory germination nor the rates of growth processes decreased. Thus, long-term storage of seeds under permafrost conditions favored the preservation of their viability (germination) and can be offered as a promising method of seed storage.